Diet Elimination of The Breastfeeding Mother in Treating Allergies of Infants Ages 0-12 - Cathryne, Joice; Kartika, Lia (UIMA Press, 2021)
Background: Breast Milk (BM) is the primary nutrient that must be given to babies. Complete breast milk nutrients help the babies' growth, development, and boost immunity. Some data found that breastfeeding triggers infant allergies. Objectives: To critically appraise the evidence of the effectiveness of the breastfeeding mother's elimination diet (ED) in treating allergies of infants ages 0-12. Methods: A literature search was conducted for publication during 2016 – 2021 using the following databases: EBSCO, Google Scholar, and Proquest with the search keywords of